MASHLAHAH DALAM AL-QURAN (SEBUAH PENGANTAR) - Zul Ikromi (UIN SUSKA RIAU, 2015)
Indeed, the main goal of the revelation of Islamic teachings in the Koran is to create goodness (mashlahah) for mankind in the form of happiness and peace.Besides, it rejects all forms of evil (mafsadah) of misery and destruction for living in the world and also in the Hereafter.